2014
DOI: 10.4136/ambi-agua.1474
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade espaço-temporal da temperatura e difusividade térmica do solo de Lagoa Seca-PB

Abstract: O objetivo deste trabalho foi investigar a variabilidade espaço-temporal da temperatura e difusividade térmica do solo de Lagoa Seca-PB. Para alcançar este objetivo foram utilizados sensores de temperatura, programados a operar ininterruptamente ao longo dos ciclos diários, instalados em quatro profundidades distintas do solo. Estes, por sua vez, monitoraram o comportamento térmico do solo durante todo o ano de 2010 e 2011. A fim de estimar a difusividade térmica do solo foram empregados três métodos distintos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Therefore, the 0.10 m layer for all months showed a soil temperature fluctuation closer to the 0.05 m layer than to the 0.20 m layer. Similar results were found by Belan et al (2013) and Diniz et al (2014), who found that maximum temperatures occurred at different times. The delay from surface to deeper depths showed that the heat wave requires a certain time period to propagate in the soil because of slow heat conduction capacity through the vertical soil profile, as mentioned above.…”
Section: Rev Bras Cienc Solo 2018;42:e0170221supporting
confidence: 79%
See 3 more Smart Citations
“…Therefore, the 0.10 m layer for all months showed a soil temperature fluctuation closer to the 0.05 m layer than to the 0.20 m layer. Similar results were found by Belan et al (2013) and Diniz et al (2014), who found that maximum temperatures occurred at different times. The delay from surface to deeper depths showed that the heat wave requires a certain time period to propagate in the soil because of slow heat conduction capacity through the vertical soil profile, as mentioned above.…”
Section: Rev Bras Cienc Solo 2018;42:e0170221supporting
confidence: 79%
“…In another study developed by Diniz et al (2014) in the state of Paraiba, Brazil, considering depths from 0.05 to 0.15 m, October showed the lowest thermal diffusivity (0.59 × 10 -6 m 2 s -1 ) and June showed the highest (1.11 × 10 -6 m 2 s -1 ) in 2010. According to the authors, June had the greatest rainfall; therefore, the soil pore space was filled with water, providing greater heat conduction capacity.…”
Section: Rev Bras Cienc Solo 2018;42:e0170221mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it can be assumed that the maximum magnitude occurs at 1:00 p.m. [23][24][25]. In this context, Equation ( 24) can be rewritten for the surface (z = 0):…”
Section: Phase Constantmentioning
confidence: 99%